Time restricted feeding modifies leukocyte responsiveness and improves inflammation outcome - Ella, Krisztina; Sűdy, Ágnes R.; Búr, Zsófia; Koós, Bence; Kisiczki, Ármin S.; Mócsai, Attila; Káldi, Krisztina (Frontiers in Immunology, 2022)
Time restricted eating, the dietary approach limiting food intake to a maximal 10-hour period of daytime is considered beneficial in metabolic dysfunctions, such as obesity and diabetes. Rhythm of food intake and parallel changes in serum nutrient levels are also important entrainment signals for the circadian clock, particularly in tissues involved in metabolic regulation. As both the metabolic state and the circadian clock have large impact on immune functions, we investigated in mice whether time restricted feeding (TRF) affects systemic inflammatory potential. TRF slackened the symptoms in K/BxN serum-transfer arthritis, an experimental model of human autoimmune joint inflammation. Compared to ad libitum conditions TRF reduced the expression of inflammatory mediators in visceral adipose tissue, an integrator and coordinator of metabolic and inflammatory processes. Furthermore, TRF strengthened the oscillation of peripheral leukocyte counts and alongside decreased the pool of both marginated and tissue leukocytes. Our data suggest that the altered leukocyte distribution in TRF mice is related to the attenuated expression of adhesion molecules on the surface of neutrophils and monocytes. We propose that TRF modifies both rhythm and inflammatory potential of leukocytes which contribute to the milder reactivity of the immune system and therefore time-restricted eating could serve as an effective complementary tool in the therapy of autoinflammatory processes.